(untitled) (Research, Society and Development, 2022)
Athletics is a sport that contains the basic movements of the human being and involves endurance, physical strength and skill. To evaluate the performance of athletes, jump tests can be used, as they are related to performance in the race besides being safe and effective alternatives. To verify the performance indexes of athletes in jump tests while trying to establish possible influencing factors of these results. 20 men and 9 women (averages of 17.28±6.07 years of age, 168.45±7.56 centimeters of height and 58.17±7.28 kilograms of body mass of the various types of athletics performed three types of jumps - Countermovement, Jump Jump and Horizontal Jump - which were filmed through the My Jump 2 application® to obtain performance values. Cmj height: Sprinter: 36.33±7.93 cm, Jumper: 35.47±8.4 cm; Double Modality: 33.45±14.73 cm. DJ Height: Sprinter: 35.18±6.62 cm, Jumper: 34.40±13.97 cm; Double Modality: 34.20±4.66 cm. Horizontal Jump Distance: Sprinter: 207±32 cm; Jumper: 230±42 cm; Double Mode: 208±43 cm. The differences between the groups of modalities in which the athletes were divided did not show a significant correlation between the performance in the jumps performed.